Flying Squad response to medical emergencies. Issue 1 (March 1990) - Barton, D; Pritty, P
Abstract : The Flying Squad of the Accident and Emergency Department, of the Derbyshire Royal Infirmary, was established in 1955 by Collins. The initial function was to provide emergency care to victims of industrial accidents. However, the spectrum of emergencies they now respond to has expanded and includes predominantly road traffic accidents and medical emergencies. Despite the proliferation of Flying Squads their benefit has been difficult to quantify even in a trauma setting (Robertson & Steedman, 1985; Gorman & Coals, 1983). The outcome in medical emergencies is reported as dismal (Robertson & Steedman, 1985; Rowley & Collins, 1979) yet the number of calls for the flying squad to attend medical emergencies are many. Previous reports have recorded 20-30% of Squad calls responding to medical emergencies (Gorman & Coals, 1983; Rowley & Collins, 1979; Steedman & Robertson, 1986; Harrop & Bodiwala, 1983).